Influence of contact medium and surfactants on carbon dioxide clathrate hydrate kinetics - Kumar, Asheesh; Sakpal, Tushar; Linga, Praveen; Kumar, Rajnish (Fuel, 2013)
Carbon dioxide (CO2) hydrate formation kinetic was investigated in a fixed bed crystallizer at constant pressure (3.55 MPa) and temperature (274 K). Porous media of three different silica gels were used, with a mesh size of 60-120, 100-200 and 230-400 having different surface area. The observed trends indicate that silica gel with larger surface area leads to higher gas consumption as well as reduces the induction time. The effect of pore diameter and particle size distribution has already been reported in a previous study [1]. In this study the effect of additives on hydrate formation kinetics were also investigated. The additives studied were nonionic surfactant Tween-80 (T-80), cationic dodecyltrimethylammonium chloride (DTACl) and anionic Sodium Dodecyl Sulphate (SDS). Out of the three surfactants used in this study, SDS was found to be most effective in enhancing the rate of hydrate formation as well as reducing the induction time. The current result shows significant improvement in water to hydrate conversion in silica gel media compared to quiescent water or surfactant-water system under similar conditions. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide capture; Clathrate hydrate; kinetics; Silica gel; Surfactants

Impact of experimental pressure and temperature on semiclathrate hydrate formation for pre-combustion capture of CO2 using tetra-n-butyl ammonium nitrate - Babu, Ponnivalavan; Datta, Stuti; Kumar, Rajnish; Linga, Praveen (Energy, 2014)
TBANO(3) (tetra-n-butyl ammonium nitrate) is a promising liquid phase promoter for capturing CO2 via HBGS (hydrate based gas separation) technology. In this study, the impact of experimental pressure and temperature on formation of mixed CO2-H-2-TBANO(3) semiclathrate hydrate for the optimum 1.0 mol% TBANO(3) reported by Babu et al. [1] was investigated. Experimental pressures of 3.0, 4.5 and 6.0 MPa and temperatures of 274.2, 276.2 and 278.2 K were employed. Irrespective of the experimental pressure, shorter induction time was observed for experiments conducted at 274.2 K when compared to the experiments at other temperatures. At a given pressure, the total gas uptake increased with increase in experimental temperature. Similarly at a given temperature, the total gas uptake increases with an increase in pressure. Higher rate of hydrate formation was observed at experimental pressure of 6.0 MPa than at 3.0 and 4.5 MPa irrespective of the experimental temperature. The CO2 composition in hydrate was between 87.5 and 93.2 mol%. Finally, the gas consumption for 1.0 mol% TBANO(3) as promoter was much higher than other promoters of quaternary salts like tetra-n-butyl ammonium bromide and tetra-n-butyl ammonium fluoride at comparable concentration and driving force. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide capture; Clathrate process; Gas hydrates; Semi-clathrates

Impact of fly ash impurity on the hydrate-based gas separation process for carbon dioxide capture from a flue gas mixture - Kumar, Asheesh; Sakpal, Tushar; Linga, Praveen; Kumar, Rajnish (Industrial & Engineering Chemistry Research, 2014)
The hydrate-based gas separation (HBGS) process for gas mixtures of CO2 + N-2 (flue gas) and CO2 + H-2 (fuel gas) has proven to be very efficient and highly selective for CO2 capture. In addition to CO2 and N-2, flue gas from coal-based thermal power stations can contain impurities such as nitrogen oxides (NOx), sulfur oxides (SOx), and fly ash. In this work, the impact of fly ash on the HBGS process efficiency was investigated. Tetrahydrofuran (THF, 1 mol %) was used as a thermodynamic promoter, and sodium dodecyl sulfate (SDS) and sodium dodecyl benzenesulfonate (SDBS) (anionic surfactants) were used as kinetic promoters. Whereas the use of THF in the HBGS process reduces the operating pressure significantly, both SDS and SDBS were found to enhance the rate of hydrate formation. It was observed that the hydrate equilibrium conditions did not change in the presence of fly ash. However, the presence of fly ash enhanced the separation efficiency of the HBGS process by reducing the induction time and increasing the kinetics of hydrate formation. Therefore, the presence of fly ash in a flue gas mixture is not detrimental to the HBGS process, which is a positive factor for the capture and geological sequestration of CO2 in the form of gas hydrates.

Impact of pressure and temperature on tetra-n-butyl ammonium bromide semi-clathrate process for carbon dioxide capture - Babu, Ponnivalavan; Chin, Weng Inn; Kumar, Rajnish; Linga, Praveen (International Conference on Applied Energy, ICAE2014, 2014)
The pre-combustion capture of CO2 in an IGCC power plant employing the hydrate based gas separation (HBGS) process is a novel method currently receiving attention around the world. Tetra-n-butyl ammonium bromide (TBAB) is a promoter that has been shown to improve the efficiency of hydrate formation. In this study, the effect of temperature and pressure on 0.3 mol% TBAB solution is investigated. The induction time for the experiments conducted at 6.0 MPa and 274.8 K was found to be lower, while nucleation became increasingly random as temperature is increased and pressure is reduced. Total gas uptake and normalized rate of hydrate formation (NR5) is also the highest for the experiments conducted at 6.0 MPa and 274.8 K. However, it was found that the hydrate phase CO2 composition remains relatively constant at both reduced temperatures and pressures. (C) 2014 The Authors. Published by Elsevier Ltd.
Keywords: Carbon dioxide capture; Clathrate process; Gas hydrates; Gas separation; Promoters; tetra-n-butyl ammonium bromide